Efektivitas Model Permainan Kolaboratif dalam Meningkatkan Sikap Penghargaan Keragaman pada Peserta Didik Sekolah Dasar - Izzah, Nur Rohmatul; Fatmawati, Fatmawati; Syaikhon, Muhammad (JURNAL PENA EDUKASI, 2026)
Abstract: As a multicultural nation, Indonesia faces persistent challenges in fostering inclusive and tolerant attitudes among young learners. Elementary education represents a critical stage for shaping children’s social values and attitudes toward diversity. This study examines the effectiveness of a jigsaw-based collaborative game model in enhancing students’ appreciation of diversity in early elementary classrooms. A quantitative approach was employed using a quasi-experimental non-equivalent control group pretest–posttest design. Two intact classes participated, consisting of an experimental group implementing the jigsaw game model and a control group receiving conventional instruction. Data were collected using a validated Likert-scale instrument and analyzed through independent sample t-tests on normalized N-Gain scores. The results indicate that students in the experimental group achieved a significantly higher mean N-Gain score (0.75, high category) compared to the control group (0.33, moderate category) (p < 0.05). These findings provide empirical evidence that collaborative jigsaw games are effective in strengthening students’ attitudes of respect for diversity and can serve as an inclusive instructional strategy in multicultural elementary school contexts.Keywords: diversity; elementary education; jigsaw; collaborative learning; respect; toleranceAbstrak: Indonesia sebagai negara multikultural menghadapi tantangan dalam menumbuhkan sikap inklusif dan toleran pada peserta didik sejak pendidikan dasar. Penelitian ini bertujuan menguji efektivitas model permainan kolaboratif berbasis jigsaw dalam meningkatkan sikap penghargaan terhadap keragaman pada peserta didik kelas awal Sekolah Dasar. Penelitian menggunakan pendekatan kuantitatif dengan desain eksperimen semu non-equivalent control group pretest–posttest. Sampel terdiri atas dua kelas, yaitu kelompok eksperimen yang menerapkan permainan jigsaw dan kelompok kontrol dengan pembelajaran konvensional. Data dikumpulkan menggunakan instrumen skala Likert yang telah memenuhi kriteria validitas dan reliabilitas, kemudian dianalisis menggunakan uji-t terhadap skor N-Gain ternormalisasi. Hasil analisis menunjukkan bahwa kelompok eksperimen memperoleh rata-rata N-Gain sebesar 0,75 (kategori tinggi), secara signifikan lebih tinggi dibandingkan kelompok kontrol dengan N-Gain sebesar 0,33 (kategori sedang) (p < 0,05). Temuan ini menunjukkan bahwa model permainan kolaboratif berbasis jigsaw efektif dalam meningkatkan sikap penghargaan terhadap keragaman, sehingga berpotensi menjadi strategi pembelajaran inklusif yang relevan untuk pendidikan dasar di lingkungan multikultural.Kata kunci: jigsaw; keragaman; pembelajaran kolaboratif; penghargaan; sekolah dasar; toleransi